2007
DOI: 10.3892/ijo.30.4.849
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glycolytic enzymes is increased in pancreatic cancerous tissues as evidenced by proteomic profiling by two-dimensional electrophoresis and liquid chromatography-mass spectrometry/mass spectrometry

Abstract: The prognosis of patients with pancreatic cancer is very poor because of late diagnosis and the lack of response to various therapies. We tried to identify proteins that might be available for early diagnosis and effective therapies by proteomic profiling of pancreatic cancer tissues. Pancreatic cancerous and paired non-cancerous tissues obtained from surgical resections or autopsies of 10 patients were analyzed by two-dimensional gel electrophoresis. The differential display showed 11 spots whose expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 40 publications
(41 reference statements)
7
88
0
Order By: Relevance
“…α-enolase is a plasminogen-binding protein and also appears to play a major role in the promotion of plasminogen activation by leukocytic cells [74]. Peptidylprolyl isomerase (cyclophilin A) has been associated with a number of cancer histiotypes including breast [75] and pancrease [76,77], and has been implicated in cellular resistance to hypoxia-and Cisplatininduced cell death [78] and resistance to aplidin [79]. Its secretion from regressive tumor masses has been previously been studied by MS [80] and it has been profiled as one of a number of glycolytic enzymes increased in pancreatic cancerous tissues [76].…”
Section: Non-classical Secretionmentioning
confidence: 99%
“…α-enolase is a plasminogen-binding protein and also appears to play a major role in the promotion of plasminogen activation by leukocytic cells [74]. Peptidylprolyl isomerase (cyclophilin A) has been associated with a number of cancer histiotypes including breast [75] and pancrease [76,77], and has been implicated in cellular resistance to hypoxia-and Cisplatininduced cell death [78] and resistance to aplidin [79]. Its secretion from regressive tumor masses has been previously been studied by MS [80] and it has been profiled as one of a number of glycolytic enzymes increased in pancreatic cancerous tissues [76].…”
Section: Non-classical Secretionmentioning
confidence: 99%
“…We have previously demonstrated that TAGLN contributes to the enhanced migration of hypoxic human pulmonary artery smooth muscle cells (hPASMCs) (10). In addition, TAGLN overexpression has been observed in gastric malignancies (11,12) and pancreatic cancer (13). Such…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of enzymes involved in the glycolytic pathway is a common feature of cancerous tissues. Increased glycolysis in cancer cells has been regarded as the result of intratumoral hypoxia and is possibly associated with tumor invasion, metastasis or resistance to therapy (37). As reported previously, GPDM participates in the reoxidation of cytosolic NADH by delivering reducing equivalents from this molecule into the electron transport chain, thus sustaining glycolysis (38).…”
Section: Discussionmentioning
confidence: 99%